How should unemployment insurance vary over the business cycle? - Serdar Birinci; Kurt See (Bank of Canada, 2020)
We study optimal unemployment insurance (UI) policy over the business cycle, using a heterogeneous agent job-search model with aggregate risk and incomplete markets. We validate the model-implied micro and macro labor market elasticities to changes in the generosity of UI benefits against existing estimates and we reconcile divergent empirical findings. We show that generating the observed demographic differences between UI recipients and non-recipients is critical for determining the magnitudes of these elasticities. We find that the optimal UI policy features countercyclical replacement rates with an average generosity that is close to current U.S. policy but that it adopts drastically longer payment durations reminiscent of European policies.
Keywords: E24; E32; J64; J65; 330; Business cycles and fluctuations; Labour markets; Fiscal policy